2021
DOI: 10.1038/s41598-020-79540-3
|View full text |Cite
|
Sign up to set email alerts
|

An atlas for human brain myelin content throughout the adult life span

Abstract: Myelin water imaging is a quantitative neuroimaging technique that provides the myelin water fraction (MWF), a metric highly specific to myelin content, and the intra-/extra-cellular T2 (IET2), which is related to water and iron content. We coupled high-resolution data from 100 adults with gold-standard methodology to create an optimized anatomical brain template and accompanying MWF and IET2 atlases. We then used the MWF atlas to characterize how myelin content relates to demographic factors. In most brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 57 publications
15
35
0
Order By: Relevance
“…These results are consistent with a pattern of brain maturation through middle age followed by a rapid decline, in agreement with postmortem observations (Peters, 2002;Tang, Nyengaard, Pakkenberg, & Gundersen, 1997). Indeed, previous studies have revealed inverted Ushape trends of MWF with age in different brain structures (Arshad et al, 2016;Dvorak et al, 2021); although MWF represents a very different metric than aggregate g-ratio, both of these indices are expected to correlate with overall extent and quality of myelination. In addition, we found that different regions exhibited similarities, as well as differences, in the associations between aggregate g-ratio and age, with most regions peaking during the fifth decade of life.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with a pattern of brain maturation through middle age followed by a rapid decline, in agreement with postmortem observations (Peters, 2002;Tang, Nyengaard, Pakkenberg, & Gundersen, 1997). Indeed, previous studies have revealed inverted Ushape trends of MWF with age in different brain structures (Arshad et al, 2016;Dvorak et al, 2021); although MWF represents a very different metric than aggregate g-ratio, both of these indices are expected to correlate with overall extent and quality of myelination. In addition, we found that different regions exhibited similarities, as well as differences, in the associations between aggregate g-ratio and age, with most regions peaking during the fifth decade of life.…”
Section: Resultssupporting
confidence: 90%
“…Further, our results indicate a quadratic association between MVF and age in all white matter regions (Table 2 and Figure 5b). These results agree with our and others' recent studies indicating an inverted Ushape association of myelin content with age in several white matter regions (Arshad et al, 2016;Dvorak et al, 2021). The quadratic association between MVF and age is attributed to the process of myelination from youth through middle age, followed by demyelination in later years (Arshad et al, 2016;Bartzokis et al, 2010); this pattern is in agreement with postmortem observations (Peters, 2002;Tang et al, 1997).…”
Section: Avf and Mvfsupporting
confidence: 93%
See 1 more Smart Citation
“…However, previous MWI studies demonstrated good intersite (mean MWF coefficient of variation (COV) = 4.68 %) and inter-vendor (mean MWF COV = 2.77 %) reproducibility. 18,33 34 disease duration appears to play a more important role in ProgMS than RRMS in our cohorts (Figure 3); understanding the impact of these different characteristics of the groups warrants further exploration in a larger cohort. Another factor worthy of consideration is that we scanned the cervical cord, particularly C2/C3 level, rather than the whole spinal cord.…”
Section: Resultsmentioning
confidence: 82%
“…On the basis of imaging studies, convincing evidence points towards a relation between white matter integrity, plasticity and intellectual development of the central nervous system during child-and adulthood (Wang and Young, 2014;Bells et al, 2019). Apart from age-related changes of white matter throughout lifespan, which peak in the third and decline from the fifth decade onward (Dvorak et al, 2021), longitudinal neuroimaging studies revealed an effect of experience on white matter that can be traced with diffusion weighted imaging (Zatorre et al, 2012). Investigations in animals and humans show that white matter changes dynamically and dependent of the standardized study-experience in vivo following training (Keller and Just, 2009;Blumenfeld-Katzir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%